A lattice Boltzmann model for simulating gas transport in coal nanopores considering surface adsorption and diffusion effects. (15th May 2023) - Li, Wei; Yang, Kang; Deng, Dong; Zhao, Changxin; Yang, Shilong; Cheng, Yuanping; Lu, Shouqing
Graphical abstract: Highlights: A lattice Boltzmann model considering surface adsorption and diffusion effects is developed. Multiple mechanisms of gas flow in coal nanopores are analyzed, including viscous flow, enhanced gas slippage and surface diffusion. The effects of adsorbed gas surface diffusion and adsorption on bulk phase gas flow in coal nanopores are investigated. The main control gas flow mechanisms in the process of gas extraction are highlighted. Abstract: The gas flow in coal is extremely complicated as a combined results of multiple flow mechanisms and complex pore structures. Comprehensive understanding of gas flow behaviors in coal is of great importance for the prediction of coalbed methane (CBM) production and the elimination of gas-induced disasters in coal mines. Based on the lattice Boltzmann method (LBM), this study constructs a LB model considering surface adsorption and diffusion effects, which involves multiple mechanisms of gas flow, including viscous flow, enhanced gas slippage (gas slippage is enhanced by surface diffusion) and surface diffusion. The results show that in micropores (<2 nm) and mesopores (2–50 nm), under the effect of adsorbed gas, bulk gas flow velocity increases at a low pressure but decreases at a high pressure. Adsorbed gas surface diffusion permeability, enhanced gas slippage permeability and viscous flow permeability decrease with the rise of pore pressure. In nanopores in coal reservoirs, surface diffusion more significantly enhances gas slippage at a low pressure and in smaller pores. Besides, in the flow calculation, gas slippage without the considering effect of adsorbed gas and Knudsen diffusion can replace each other. According to the results from the LB model, the apparent diffusion coefficients of gas in coal particles decreases with the increase of pore pressure in smaller pores(<10 nm) but increases in larger pores(>10 nm). The study further investigates flow mechanisms controlling the CBM extraction yield in different extraction stages. In the early stage of extraction, the CBM extraction yield is controlled by Darcy seepage in fractures; in the middle stage, it is controlled by viscous flow in larger matrix pores; in the late stage, it is controlled by gas diffusion induced by the superposition of surface diffusion and enhanced gas slippage in matrix micropores and mesopores.